Analysis Of Web-Based Management Information System Design To Improve The Effectiveness And Efficiency Of The New Employee Recruitment Process At One Of The Fast Moving Consumer Goods (FMCG) Companies In DKI Jakarta - Inneke Vincentia (Journal Research of Social Science, Economics, and Management, 2023)
The process of recruiting new employees is an important aspect in human resource management in the company. In the era of digitalization and the development of information technology, web-based management information systems can be a solution to improve the effectiveness and efficiency of the recruitment process. The purpose of this study is to investigate the design of a web-based management information system that can improve the effectiveness and efficiency of the recruitment process of new employees in FMCG companies in DKI Jakarta. This study used qualitative research methods. Data collection techniques are carried out by observation, interviews and literature studies. The process of designing an employee recruitment selection system using UML (Unified Modelling Language) Tools namely Use Case Diagram, Activity Diagram, Sequence Diagram with Visual Paradigm software. The results of the study show that the ability to select applicant data becomes more effective in terms of time and the amount of work completed when using technology than just using human labor. In the process, humans professionally and as individuals will adapt and feel helped by technology. Therefore, companies need to make changes to balance the era of technological disruption that occurs.